2019
DOI: 10.2196/12660
|View full text |Cite|
|
Sign up to set email alerts
|

Computer-Aided Detection for Breast Cancer Screening in Clinical Settings: Scoping Review

Abstract: Background With the growth of machine learning applications, the practice of medicine is evolving. Computer-aided detection (CAD) is a software technology that has become widespread in radiology practices, particularly in breast cancer screening for improving detection rates at earlier stages. Many studies have investigated the diagnostic accuracy of CAD, but its implementation in clinical settings has been largely overlooked. Objective The aim of this scoping review wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…According to their results, the radiologists were more favorable to double reading, even though most of them perceived that DDSSs were better at improving recall rates than double reading. The meta-analysis proposed by Masud et al (2019), on the use of DDSSs in radiology departments, showed similar results on the low acceptability of DDSSs despite an improvement of performances perceived by radiologists.…”
Section: A Questionable Acceptabilitymentioning
confidence: 67%
See 1 more Smart Citation
“…According to their results, the radiologists were more favorable to double reading, even though most of them perceived that DDSSs were better at improving recall rates than double reading. The meta-analysis proposed by Masud et al (2019), on the use of DDSSs in radiology departments, showed similar results on the low acceptability of DDSSs despite an improvement of performances perceived by radiologists.…”
Section: A Questionable Acceptabilitymentioning
confidence: 67%
“…To sum-up, although there are exceptions in specific situations, it appears that DDSSs are generally poorly accepted in customary situations, where support appears to be redundant with physicians' capabilities (Masud et al, 2019). It hence appears that we are currently in a paradoxical situation.…”
Section: A Questionable Acceptabilitymentioning
confidence: 97%
“…We believe a tool like our automated segmentation method could play a role in this situation. For example, in computer‐aided detection in breast mammography, the radiologist combines their interpretation of a study with an algorithm's interpretation to develop a final read 21 . In a similar and simpler fashion, the radiologist measuring the greatest linear dimension of a VS to detect tumor growth could also run an automated segmentation protocol on the scan, and use the two sets of data to evaluate growth without resorting to time‐ and labor‐intensive manual segmentation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in computer-aided detection in breast mammography, the radiologist combines their interpretation of a study with an algorithm's interpretation to develop a final read. 21 In a similar and simpler fashion, the radiologist measuring the greatest linear dimension of a VS to detect tumor growth could also run an automated segmentation protocol on the scan, and use the two sets of data to evaluate growth without resorting to time-and laborintensive manual segmentation. For reference, it takes on average 1.34 seconds to run our segmentation algorithm on an identified VS using the graphics card described in the Materials and Methods section, versus minutes to manually segment a tumor, depending on slice thickness and tumor size.…”
Section: Discussionmentioning
confidence: 99%
“…Although our results demonstrate the feasibility of reducing unnecessary biopsies using our in vivo Raman-based tool in a typical skin cancer screening setting, we have not asked dermatologists to hypothesize about whether they would have changed their decision to biopsy if our results suggested that a biopsy was not needed. Research in other areas of medical imaging demonstrates that computer aided detection or diagnosis recommendations do not necessarily change a physician’s actions [ 30 ]. Therefore, future studies are needed on the acceptability of our tool in dermatological practice.…”
Section: Discussionmentioning
confidence: 99%